Teacher's Perspective for Thematic Learning Systems During the Covid-19 Pandemic - Nurmawati, Fulusia; Sukarno; Yulisetiani, Septi (Universitas Pendidikan Ganesha, 2022)
Covid-19 has brought comprehensive changes in the field of education such as conducting learning with a distance learning system. The main purpose of this research is to analyze the teacher's view of learning needs and explore the factors that become obstacles in online thematic learning in elementary schools. This type of research is a mixed methods research, namely qualitative and quantitative research designs. The subject of this research is to take a sample of teachers in 20 elementary schools with a population of 200 teachers with a sample of 20 teachers. The sampling method used simple random sampling. Quantitative data in the form of samples based on questionnaire scores from 5th grade teachers with a sample of 20 teachers from 20 elementary schools. Data analysis is used to draw final conclusions on the results of the data, both from interviews, observations, and documents using interactive analysis techniques, namely data collection, data condensation, data display (data display) and drawing conclusions. The results showed that the thematic learning system had not been maximally implemented in schools; it is necessary to get used to implementing an android-based system which includes zoom for face-to-face online meetings, learning materials and evaluation of learning, so that teachers can explore the learning system used during the Covid-19 pandemic. In conclusion, the learning system in thematic learning during the Covid-19 pandemic still needs to be developed and explored because there are obstacles in the implementation of the learning process.